Keberanian Dalam Memulai Bisnis E-Commerce: Mengelola Risiko Dan Sukses (Studi Kasus Mahasiswa Politeknik Negeri Bandung) - muhammad hafidz fakhrudien (Asosiasi Ahli Administrasi Indonesia, 2024)
This research was conducted with the aim of assessing the impact of courage and risk management skills on the success of e-commerce businesses among students at Bandung State Polytechnic. The research method employed was a quantitative descriptive approach, with data collected through the online distribution of questionnaires using the Google Form application to 100 respondents who are students at Bandung State Polytechnic. The gathered data was then analyzed using descriptive and multiple regression analyses conducted with SPSS software. The findings of this study indicate that both courage and risk management skills have an impact on the success of e-commerce businesses, with the risk management variable showing dominance as the most influential factor.